Implementation of rational grazing system Voisin in the farm La Gloria in the municipality of Puerto Lopez (Meta) (Revista Sistemas de Producción Agroecológicos, 2012)
This work was done on the farm La Gloria of the village Melua municipality of Puerto Lopez, Meta department, which is situated at 300 meters above sea level, with a temperature of 30 °C, relative humidity of 82%, soil prevailing in the region are loam and acid, with a 60% flat topography, 30% rolling and 10% broken. Production rates of the farm La Gloria especially the weight gains were low in a traditional grazing system, therefore, this project was to implement a rational grazing system on the farm which helped to optimize the use without significant loss of forage, likewise, contributed in improving production rates of the estate, among other benefits. Initial diagnosis was performed to check the status of the farm and as it was in terms of soil, which provided fodder for livestock, water sources and other resources to determine what conditions are going to implement the project. Was planned based on the initial diagnosis which were the best conditions for the project, as well, that a budget as approved by the parties concerned in the execution. It implemented the project of implementation of sound grazing system Voisin according to established and approved by the producer and organized the current grazing system to assist in improving production rates (weight gain) in cattle of the estate. Spending was achieved in 64 acres of producing 21 tons of meat to 52 tons in the same area, that is, 0.3 tons of meat per hectare to 0.8 tons of meat per hectare, in addition to the employees became aware of the farm La Glory in good farming practices and life sciences and related to the proper management of pastures.
Keywords: voisin rotational grazing; weight gain; cattle fattening